Application of the Composite Hydrotalcite (Mg/Al)/Chitosan as Adsorbent for the Treatment of Raw Water of Municipal Waterworks PDAM Bandarmasih - Maulana Wahyu Noor Ramadhan; Chairul Irawan; Hesti Wijayanti; Muthia Elma (Journal of Wetlands Environmental Management, 2019)
Research has been carried out about raw water treatment of PDAM Bandarmasih by hydrotalcite (Mg/Al) + chitosan (shell of haruan and papuyu fish) adsorbent reviews of decreasing dye value (PtCo), iron (Fe), and turbidity. This research intended toÂ  produce drinking water from utilization of fish shell that were still underutilized into chitosan to be matched with hydrotalcite (Mg/Al) with variations of 1, 2 and 3 grams with a duration of 24 hours. The results showed that the decrease in dyestuff value were 96.78%, 95.03% and 92.98%. Persentage decrease in iron (Fe) were 94.38%, 93.78 and 91.87% and percent of turbidity reduction were 97.98%, 79.76% and 76.56%. Best decrease in variations ofÂ  hydrotalcite (Mg/Al) + chitosan was 1 gram for a duration of 24 hours which resulted in a decrease in dyestuff, iron and turbidity of 11 PtCo, 0.047 mg/L, 0.76 NTU where the results were appropriate in the drinking water requirements in accordance with the Regulation of the Minister of Health of the Republic of Indonesia no:492/MENKES/PES/IV/2010.